THE EFFECT OF FOCUSED GAS DISTRIBUTION ON THE WORK ENERGY PARAMETERS OF THE MIDDLE-PRESSURE GAS DISTRIBUTION SYSTEMS - Ксенич, Андрій Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The normative forecasting methods of gas distribution in the middle-pressure gas supply networks, made of steel and polyethylene pipes, do not describe existent gas-dynamic processes correctly. It is proved that the error of energy parameter A calculations using the model of even continuous gas distribution along the pipeline is up to 74% depending on the pipeline operational parameters. In this paper a revised method for calculating the design and operating parameters of segments of the middle-pressure gas distribution networks is presented taking into account a model of focused gas extraction along the pipeline.